Effect of foot muscle energy technique in patients with diabetic neuropathy:a randomized controlled trial - Fayek Hammam, Radwa; Magdy Alshimy, Ahmed; Fakhrey Mosaad, Andrew Anis; Gamal Ibrahim, Maha (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2024)
Introduction. This study investigated the effect of foot muscle energy technique (MET) on nerve conduction velocity (NCV)and isometric muscle strength in patients with type 2 diabetic neuropathy (DN).Methods. Forty-four patients were randomly assigned to either the MET group (group A) or the conventional physical therapyprogram group (group B). Electrophysiological measurements, including peroneal and tibial motor NCV studies, and isometricmuscle strength using a toe strength dynamometer, were conducted. The assessment period ranged from April to November2022, with measurements taken before the first session and after 4 weeks of treatment.Results. Significant improvements were observed in post-treatment peroneal motor NCV (p < 0.001), tibial motor NCV (p < 0.001),and isometric muscle strength (p < 0.001) in group A, but not in group B.Conclusions. MET enhances motor NCV and isometric muscle strength in patients with type 2 DN.
Keywords: diabetic neuropathy; foot muscle energy technique; isometric muscle strength; motor nerve conduction velocity